Avances en el proceso de formación y actualización catastral del núcleo Hacienda La Cabaña - Girón Amaya, Edwin; Torres León, Jorge Luis; Molina Villareal, Angie; Ospina Garay, Carlos Alberto; Tovar, Juan Pablo (Boletín El Palmicultor, 2016)
Agosto 2016